1973
DOI: 10.2134/agronj1973.00021962006500060040x
|View full text |Cite
|
Sign up to set email alerts
|

Double Cropping Systems Involving No‐Tillage and Conventional Tillage1

Abstract: This study was prompted by the huge feed grain deficits which increase annually in the Southeast. The need exists to find ways of increasing grain production efficiently. Cropping‐tillage systems designed to accomplish this were studied. Soybeans [Glycine max (L.) Merr.] and grain sorghum [Sorghum bicolor (L.) Moench.] were double cropped following wheat (Triticum aestivum L.) on a Blackbelt soil. No‐tillage and conventional tillage methods were compared for soybeans and grain sorghum; Conventional tillage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 3 publications
3
38
0
Order By: Relevance
“…Similar results were reported by Langdale et al (1984), Sanford et al (1973), Elkins et al (1980), and Lal (1981. In no-till systems chemicals gave significantly better weed control because the pre-plant application of glyphosate killed existing weeds and the postemergence application of atrazine gave effective residual weed control.…”
Section: Weed Control In Sorghum 119supporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported by Langdale et al (1984), Sanford et al (1973), Elkins et al (1980), and Lal (1981. In no-till systems chemicals gave significantly better weed control because the pre-plant application of glyphosate killed existing weeds and the postemergence application of atrazine gave effective residual weed control.…”
Section: Weed Control In Sorghum 119supporting
confidence: 90%
“…They reported that grain sorghum in rotation with soybeans in double cropping systems increased yield of both sorghum and soybeans. Sanford et al (1973) studied double cropping systems involving no-till and conventional tillage and found that there were differences in time of emergence and in plant height because of soil moisture differences in the seed placement zone. Elkins et al (1980) found that no-till soybean production in grass sod was highly successful.…”
Section: Introductionmentioning
confidence: 99%
“…A Significant genotype x tillage system interaction was apparent for SMK + SS. TX835820 and TX835841 grades were Significantly lower with no-tillage systems while other cultivars produced no significant changes in grade.Key Words: Groundnut, Sclerotium rolfsii, southern blight, notillage, minimum-tillage.The use of minimum-tillage and no-tillage production practices has reduced production costs in com, grain sorghum, soybeans, and other crops (1,10,13,14,15,16,18,19,21). However, limited research (2,3,4,5,6,7,8,9,11) has been reported with the use ofno-tillage cultural practices in peanuts.…”
mentioning
confidence: 99%
“…The timing of establishing a second crop early can be important because, after 1 Dec., the rate of decline in yield with delayed sowing is about 1.3% per day for sole-crops and 0.5% per day for double-crops (Caviglia et al, 2011). Sanford et al (1973) observed that no-till double-crop systems provided the least delay in establishing a second crop. Water available to plants affected winter wheat grain production in a study of tillage and N rates on wheat production (Halverson et al, 1999).…”
mentioning
confidence: 96%